The legitimacy of the theorical, systematic and practical study of Human Rights foundation - Lima Torrado, Jesús (2016)
What this study proposes is, first, to state the essential questions the foundation of human rights. Secondly, we will answer to the problem of the theoretical, systematic and practical relevance of the foundation of human rights. It concludes with the idea of the need to base the rights from the ethics, philosophy of law, legal science and Sciences on the law as an instrument to consolidate the necessary link between theory and praxis and consequently as an instrument of guarantee rights.